A financial frontier model with bankers' susceptibility under uncertainty. (11th July 2022) - Hyun, Hans D. G.
Abstract: This article aims to refine the Post Keynesian long run financial frontier models under an intermediate run called the ' implementation period, ' the time horizon to finance and implement long run strategic plans. During this period, the availability of debt finance is crucial to bridge the time gap before future free cash flows validate the investment. Therefore, firms' long run investment plans may be modified or suspended during this time horizon subject to bankers' uncertainty perception and state of confidence, which constrain debt capacity and firms' investment decisions. Uncertainty and the measures to enhance confidence, such as banking convention, mimetic behaviours, and bankers' spontaneous optimism, are critical to determining the financial frontier because they affect the lending amount, tenor, and refinancing potential. The proposed model focussing on bankers' convention and susceptibility explains the volatile nature of the financial frontier, investment instability, downward sloping effective loan supply and credit rationing under new perspectives.